Evaluation of the intraoperative human papillomavirus test as a marker of early cure at 12 months after electrosurgical excision procedure in women with cervical high‐grade squamous intraepithelial lesion: a prospective cohort study. (25th September 2019) - Rabasa, J; Bradbury, M; Sanchez‐Iglesias, JL; Guerrero, D; Forcada, C; Alcalde, A; Pérez‐Benavente, A; Cabrera, S; Ramon y Cajal, S; Hernandez, J; Dinares, C; García, A; et al.
Abstract : Objective: To evaluate if the intraoperative human papillomavirus (IOP‐HPV) test has the same prognostic value as the HPV test performed at 6 months after treatment of high‐grade squamous intraepithelial lesion (HSIL) to predict treatment failure. Design: Prospective cohort study. Setting: Barcelona, Spain. Population: A cohort of 216 women diagnosed with HSIL and treated with loop electrosurgical excision procedure (LEEP). Methods: After LEEP, an HPV test was performed using the Hybrid Capture 2 system. If this was positive, genotyping was performed with the CLART HPV2 technique. The IOP‐HPV test was compared with HPV test at 6 months and with surgical margins. Main outcome measure: Treatment failure. Results: Recurrence rate of HSIL was 6%. There was a strong association between a positive IOP‐HPV test, a positive 6‐month HPV test, positive HPV 16 genotype, positive surgical margins and HSIL recurrence. Sensitivity, specificity, and positive and negative predictive values of the IOP‐HPV test were 85.7, 80.8, 24.0 and 98.8% and of the HPV test at 6 months were 76.9, 75.8, 17.2 and 98.0%. Conclusion: Intraoperative HPV test accurately predicts treatment failure in women with cervical intraepithelial neoplasia grade 2/3. This new approach may allow early identification of patients with recurrent disease, which will not delay the treatment. Genotyping could be useful in detecting high‐risk patients. Tweetable abstract: IOP‐HPV test accurately predicts treatment failure in women with CIN 2/3. Tweetable abstract: IOP‐HPV test accurately predicts treatment failure in women with CIN 2/3.